A comprehensive characterization of the electro-mechanically coupled properties of VHB 4910 polymer - Mokarram Hossain (Archive of Applied Mechanics, 2014)
An illustrative documentation of some standard experimental tests of electro-active VHB 4910 polymer under application of purely mechanical and electro-mechanically coupled loadings is presented. VHB 4910 is a very soft polymer that has potential applications as an electro-active polymer in the production of different types of actuators and sensors. The time-dependent viscoelastic phenomenon is ideal in polymers. Therefore, experiments with electro-mechanically coupled loads were conducted considering some standard tests that were usually used for a viscoelastic polymeric material characterization, i.e. loading-unloading tests, single-step relaxation tests, and multi-step relaxation tests. In all experimental cases, the polymer samples were pre-stretched up to several hundred per cent to make them thin enough initially so that the application of the electro-mechanically coupled load can show its effect to a larger extend. The pre-stretched samples were then subjected to various amounts of mechanical as well as coupled deformations at different strain rates. The data produced from several loading-unloading tests, single-step relaxation tests, and multi-step relaxation tests show that the electric loading has profound effect in the time-dependent behaviour of the electro-active VHB 4910 polymer. The data set either from single-step relaxation tests or multi-step relaxation tests can be used to identify electro-viscoelastic parameters for a suitable constitutive model that can capture electro-mechanically coupled behaviours of VHB 4910. For validation, loading-unloading cyclic tests data can be utilized.